Parent’s divorce in the childhood period. (Journal of Parents and Teachers, 2012)
The following article deals with the parent’s divorce when a child is in the childhood, also it talks about how the child perceives that situation and how he or she behaves. It reflects on the effects and aspects of this process through this period of life.
Keywords: Education; divorce; parents; child; childhood; preschool.